Solving Fourth Order Ordinary Differential Equation by Using Differential Transform Method - Hisamudin, Nur Fatin Kirana; Abd Latif, Noor Azliza (Enhanced Knowledge in Sciences and Technology, 2023)
In this study, Fourth Order Ordinary Differential Equation solved by using a semi analytical solution which is differential transform method. A computational works done by Maple 2022 used to obtain the approximate solutions of Fourth Order Ordinary Differential Equation and prove that it saves amount of time and less work need to do. Numerical results obtained by using DTM is compared with First Block Method (FBM) and adomian decomposition method (ADM) by previous researchers to discover the accuracy of different method with exact solutions. The result of accuracy of DTM shows that it is depends on equation of fourth order ordinary differential equation and terms in DTM. DTM have succeed in solving three examples. Furthermore, DTM is considered as one of the simplest methods to apply in solving ordinary differential equation problems.